The Influence of Packaging and Advertising Attractiveness on Purchasing Decisions for Gogotales Beauty Products on TikTok Shop - MUHIBAN, Ayi; TIARA, Tiara (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:This research was conducted on Gogotales consumers in the TikTok Shop marketplace. The aim was to determine the influence of packaging and advertising appeal on purchasing decisions, both partially and simultaneously.Methodology:The research method used in this study is descriptive and associative. The unit of analysis is the individual, namely Gogotales consumers on the TikTok Shop marketplace. The sample size for this study was 99 respondents. The sampling technique used was based on specific considerations or criteria. The analysis method used was multiple linear regression analysis, and the validity and reliability of the research instrument were also tested.Findings:Based on the research results it shows that there is a partial and simultaneous influence on the packaging variables and advertising appeal on the purchasing decision variable.Implication:The influence of packaging on purchasing decisions is 65.3%, while the influence of advertising appeal on purchasing decisions is 12.9%. The influence of packaging and advertising appeal on purchasing decisions is 78.23%.